ANALISIS TATA KELOLA KEUANGAN DESA GUNA MEWUJUDKAN GOOD VILLAGE GOVERNANCE (Studi di Desa Pleret Kecamatan Pleret Kabupaten Bantul) - Novitasari, Dini; Hilmiawan, Gigih Aulia (JURNAL EKONOMIKA, 2024)
Good governance is an important principle in effective and sustainable village government management. Good governance is fundamental to achieving sustainable development and increased village competitiveness. It also helps build trust between the village government and the community and ensures that village resources are utilised efficiently and in accordance with the public interest. This allows for a more comprehensive understanding of how village financial management is implemented. This information illustrates the importance of good financial governance in village governance in Pleret and efforts to meet officially recognised principles of governance. This is important to ensure that village funds are used to the best of their ability for the welfare of local communities.